Defining the nociceptor transcriptome - Thakur, Matthew; Crow, Megan; Richards, Natalie; Davey, Gareth I. J.; Levine, Emma; Kelleher, Jayne H.; Agley, Chibeza C.; Denk, Franziska; Harridge, Stephen D. R.; McMahon, Stephen B. (Frontiers in Molecular Neuroscience, 2014)
Unbiased ‘omics’ techniques, such as next generation RNA-sequencing, can provide entirely novel insights into biological systems. However, cellular heterogeneity presents a significant barrier to analysis and interpretation of these datasets. The neurons of the dorsal root ganglia (DRG) are an important model for studies of neuronal injury, regeneration and pain. The majority of investigators utilize a dissociated preparation of whole ganglia when studying cellular and molecular function. We demonstrate that the standard methods for producing these preparations gives a 10%-neuronal mixture of cells, with the remainder of cells constituting satellite glia and other non-neuronal cell types. Using a novel application of magnetic purification, we consistently obtain over 95% pure, viable neurons from adult tissue, significantly enriched for small diameter nociceptors expressing the voltage gated ion channel Nav1.8. Using genome-wide RNA-sequencing we compare the currently used (10% neuronal) and pure (95% nociceptor) preparations and find 920 genes enriched. This gives an unprecedented insight into the molecular composition of small nociceptive neurons in the DRG, potentially altering the interpretation of previous studies performed at the tissue level, and indicating a number of novel markers of this widely-studied population of cells. We anticipate that the ease of use, affordability and speed of this technique will see it become widely adopted, delivering a greatly improved capacity to study the roles of nociceptors in health and disease.